Adipose gene expression profiles reveal insights into the adaptation of northern Eurasian semi-domestic reindeer (Rangifer tarandus) - Weldenegodguad, Melak; Pokharel, Kisun; Niiranen, Laura; Soppela, Päivi; Ammosov, Innokentyi; Honkatukia, Mervi; Lindeberg, Heli; Peippo, Jaana; Reilas, Tiina; Mazzullo, Nuccio; Mäkelä, Kari A.; Nyman, Tommi; et al.
Reindeer (Rangifer tarandus) are semi-domesticated animals adapted to the challenging conditions of northern Eurasia. Adipose tissues play a crucial role in northern animals by altering gene expression in their tissues to regulate energy homoeostasis and thermogenic activity. Here, we perform transcriptome profiling by RNA sequencing of adipose tissues from three different anatomical depots: metacarpal (bone marrow), perirenal, and prescapular fat in Finnish and Even reindeer (in Sakha) during spring and winter. A total of 16,212 genes are expressed in our data. Gene expression profiles in metacarpal tissue are distinct from perirenal and prescapular adipose tissues. Notably, metacarpal adipose tissue appears to have a significant role in the regulation of the energy metabolism of reindeer in spring when their nutritional condition is poor after winter. During spring, genes associated with the immune system are upregulated in the perirenal and prescapular adipose tissue. Blood and tissue parameters reflecting general physiological and metabolic status show less seasonal variation in Even reindeer than in Finnish reindeer. This study identifies candidate genes potentially involved in immune response, fat deposition, and energy metabolism and provides new information on the mechanisms by which reindeer adapt to harsh arctic conditions. 2021